Self-renewal capacity of semi-differentiated CD8+ T cells sustains long-term protective responses in chronic persistent infection - Morrot, Alexandre (Annals of Translational Medicine, 2017)
CD8+ T lymphocytes have a major role in the elimination of target cells infected by intracellular pathogens, and transformed cells expressing oncoantigens. This happens when host nucleated cells are able to present proteasome-derived antigens or indirectly cross-presented peptide antigens in association with major histocompatibility complex (MHC) class I molecules (1). Upon recognition of the MHC-peptide complexes by CD8+ T cells via their antigen receptors (TCR), cytotoxic lymphocytes release granules containing perforins and granzymes that cause direct damage to target cells, as well as expressed factors such as the Fas ligand and tumor necrosis factor-alpha (TNF-α) that induce apoptosis, thus preventing the spread of infection or tumor growth (2). It is noteworthy that the function of CD8+ T lymphocytes is not limited to eliminating target cells, these cells also participate in other mechanisms of host defense, mainly through the production of interferon-gamma (IFN-γ). IFN-γ has the ability to directly inhibit viral replication, activate macrophages by increasing its cytotoxic and antigen presenting capacity, and may further induce the synthesis of class I MHC molecules as well as other proteins involved in antigen processing and presentation (2).